Do demographic factors and a health-promoting lifestyle influence the self-rated health of college nursing students? - Susan Ka Yee CHOW; Kin-Man LAM; Shih-Hung LIE; Ka-Chun MAK; Ka-Chun MONG; Chun-Man SO; Wai-Yip YUEN (BMC, 2018)
Abstract Background To adopt a healthy lifestyle is considered an essential component of nursing education. Self-rated health is a subjective assessment of health status and is consistent with objective health status. Previous studies have shown an association between self-rated health and engagement in a healthy lifestyle. Nursing students need to feel good about their subjective health status and to be able to adopt health improvements in their lifestyle before attempting to disseminate health messages to clients. The aims of this study were to compare the difference in self-rated health and health promotion lifestyle profile between senior and junior nursing students, describe correlations between self-rated health and health promotion lifestyle profile, and identify the predictors of self-rated health. Methods A cross-sectional descriptive survey was adopted. The study sample consisted of 314 junior and senior year nursing students from a tertiary institution. The self-reported questionnaire consisted of a single-item question to examine their self-rated health. The Health Promoting Lifestyle Profile-II: Chinese version short form (HPLP-IICR) was used to investigate the health-promoting lifestyles of the students. Descriptive statistics, Mann-Whitney U test, Chi-square test, Fisher's exact test, Spearman's correlation, and ordinal logistic regression were used to analyze the data. Results The median scores for self-rated health were 3 (Mean 3.26, IQR 3-4) and 3 (Mean 3.19, IQR 3-4) out of 5 for Year 2 and Year 5 students, respectively, with no significant difference between the two groups. The two groups of students showed no significant differences in overall score and in most subscales of the HPLP-IICR. An ordinal logistic regression showed that those students with higher health management score (OR: 1.12, 95% CI: 1.04-1.21) and who had experienced no family conflicts in the recent month than having family conflict (OR: 1.64, 95% CI: 1.01-2.66) were more likely to have higher self-rated health. Conclusion Nursing education and clinical practice can undoubtedly increase the health knowledge of students, but may not lead to changes in actual health-promoting behaviours. Students with a higher health management score and no family conflicts are more likely to give a positive appraisal of their health status.